Interleukin-21 expression in hippocampal astrocytes is enhanced following kainic acid-induced seizures. (1st February 2016) - Xiong, Xiao-Yi; Wang, Ting-Gang; Yang, Mei-Hua; Meng, Zhao-You; Yang, Qing-Wu; Wang, Fa-Xiang
Abstract : Objective: Interleukin-21 (IL-21) is a cytokine that is an important modulator of immune responses. However, its roles in epilepsy are not completely clear. Here, we investigated the expression and distribution of IL-21 in a kainic acid (KA)-induced acute seizure mouse model. Materials and methods: Mice ( n  = 146) were randomly divided into an age-matched group, PBS injection group, and a KA injection group. The KA-injected mice were evaluated at 1, 3, and 24 h post-injection. IL-21 mRNA and protein expression levels were measured using RT-PCR and western blotting. Immunohistochemistry and immunofluorescence staining were performed to further characterize the pattern and distribution of IL-21 expression. Results: The IL-21 mRNA and protein expression levels in the hippocampal tissues of the KA-treated mice were significantly increased as early as 1 h compared with the age-matched mice and PBS-treated mice. After this time point, the expression was reduced, but it remained higher than the level in the PBS-treated mice ( p  < 0.01). Immunohistochemical staining showed that IL-21 expression was distributed throughout the hippocampus, including areas CA1 and CA3, the dentate gyrus and the hilus. Moreover, immunofluorescence further showed that in the hippocampi of the KA-treated mice, IL-21 was mainly expressed in GFAP-positive astrocytes rather than in NeuN-positive neurons or CD11b-positive microglia. Significance: Our data suggest that an increase in astrocyte-derived IL-21 expression in hippocampal subregions following KA-induced seizures may have potent regulatory effects on epileptogenesis.